ANALYSIS AND DEVELOPMENT OF COPPER RECYCLING OF DEAD COPPER-CONTAINING CATALYSTS - O. S. Komarov; I. V. Provorova; V. I. Volosatikov; D. O. Komarov; N. I. Urbanovich (Литьë и металлургия)
The technology of processing of copper-bearing dead catalysts, which includes leaching and deposition of copper by means of electrolysis and also their application in composition of the mixture for alloy doping is offered.